1995
DOI: 10.1007/s002040050229
|View full text |Cite
|
Sign up to set email alerts
|

The international validation study of the acute toxic class method (oral)

Abstract: An alternative to the oral LD50 test, the acute toxic class (ATC) method (oral), was validated with 20 substances in an international collaborative study with nine laboratories in five countries. The ATC method is a stepwise procedure with the use of three animals per step. It has been designed with three fixed doses (25, 200 and 2000 mg/kg). In general, this testing is sufficient for allocation to the toxicity classes of the majority of the international classification systems currently in use. The selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…Animals were fed ad libitum. Body weights of animals were measured at the beginning and at the end of the study (Schlede et al, 1995). All animals were sacrificed on the 91st day.…”
Section: Subchronic Toxicity Studiesmentioning
confidence: 99%
“…Animals were fed ad libitum. Body weights of animals were measured at the beginning and at the end of the study (Schlede et al, 1995). All animals were sacrificed on the 91st day.…”
Section: Subchronic Toxicity Studiesmentioning
confidence: 99%
“…The result of the acute toxicity study showed mortality at highest dose of up to 2900mg/kg indicating that the LD 50 of pirimiphos methyl is 2154mg/kg. This shows that pirimiphos methyl is not safe for oral usage and according to Organization for Economic Cooperative and Development (OECD) standard for ranking toxic substances [22], any substance whose LD 50 is greater than 500mg/kg and less than 5000mg/kg can be ranked under category 4 of the OECD guidelines for acute toxicity and can be said to be slightly toxic if swallowed [23].…”
Section: Discussionmentioning
confidence: 99%
“…Further hydrolysis of either intermediate results in the production of arginine, which is then further converted to ornithine and urea, following normal amino acid catabolism via the urea and citric acid cycles resulting in the formation of 14 Ccarbon dioxide and 14 C-urea, which are excreted in the expired air and in urine respectively. The ornithine could either be degraded further to citrulline and other amino acids in the urea cycle or to the metabolic intermediate α-ketoglutarate, which could then enter the citric acid cycle with subsequent metabolism to carbon dioxide (Voet and Voet 1990;Schlede et al, 1994). In another study reported by the applicant the pharmacokinetics of ethyl-Να-lauroyl-L-arginate in rats was characterised.…”
Section: Absorption Distribution Metabolism and Excretionmentioning
confidence: 99%